Implementasi AI Pendeteksi Pola Gerak Tangan pada Game “Pong Ball” dengan Menggunakan Algoritma Convolutional Neural Network - Hakam Fardana Muhammad; Muhammad Alfa Rizky Valentino; Wahyu S. J. Saputra (Fakultas Teknologi dan Informatika, 2022)
Keyboard, mouse, and joystick are hardware devices that are often used for interaction between humans and computers which are mechanical. Although accurate, the model of the interaction method is not natural as humans interact with each other. To be able to operate, it is necessary to have direct contact between the user and the computer. The thing studied here is the pattern of hand movements. This was investigated by using a program with the help of a webcam camera to perform hand object recognition. hand motion pattern detection is implemented using the cvzone library and the Convolutional Neural Network algorithm. The application of the accuracy of the program data made is by playing the game